As raízes históricas da política criminal na legislação e nas práticas de atendimento ao adolescente em conflito com a lei - Cruz, Ana Vládia Holanda (2014)
This thesis investigates the historical influence of the criminal policy in the context that shapes the first specific law for children and adolescents in Brazil, the 1927 Children's Code, a standard that inaugurates the conceptual scission between children and "minor" and their different treatment by the State. The study addresses the demand for order in the context of changes in the working world in the transition from the slave system to the capitalist mode of production, and the corresponding disciplinary and punitive control mechanisms directed to the segment of childhood and adolescence. The theoretical route proposes a questioning of the political construction of law and justice, as well as the conformation of the punitive techniques, and the construction of the stereotype of the "delinquent", prime target of the criminal policy, focusing on the process of criminalization of the segment in question through the confrontation of the Critical perspective with the approaches of Classical and Positive schools. This research shows the imposition of a bourgeois morality that obscures the social conflict attributing it to people isolated by the criminalization of their conduct; and points out that the historical forms of selective social control were greatly influenced by psychiatry and psychology, either by the elaboration of the image of the "delinquent" or by the expected performance of custodial institutions. Finally, the developments and the permanence of the historical roots of the criminal policy are problematized, relating them to the difficulties currently encountered in the consolidation of the legal garantism paradigm proposed by the Children and Adolescent Statute.